(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Viral hepatitis is an infectious disease of viral origin characterized by general intoxication, jaundice (or non-jaundiced forms), liver damage, and metabolic disorders. The term “viral hepatitis” includes all types of viral hepatitis—A, B, C, D, and E. Viral hepatitis is an acute infectious disease that manifests with liver cell damage, general intoxication symptoms, yellowing of the skin and mucous membranes, dark-colored urine (resembling “beer”), clay-colored stools, and enlargement of the liver, sometimes accompanied by spleen enlargement.